PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN TANAMAN KENIKIR DALAM UPAYA PENCEGAHAN KANKER DI RW16 DAN 17 KELURAHAN CIPAGERAN KECAMATAN CIMAHI UTARA - Eem Hayati; Betty Nurhayati; Sonny Feisal Rinaldi (Poltekkes Kemenkes Bandung, 2022)
Cancer is a disease that occurs due to the uncontrolled growth of abnormal cells, causing normal body tissues to be damaged. There are several ways that can be done to prevent cancer, including paying attention to and implementing a healthy diet and lifestyle. Some medicinal plants have the potential as anti-cancer that has a cytotoxic effect, one of which is kenikir. Kenikir leaves contain active compounds of alkaloids, polyphenols, saponins, tannins and flavonoid glycosides quercetin. The results of previous studies by several researchers showed that several methanolic extracts from kenikir leaves were known to have a cytotoxic effect on T47D cells and kenikir ethanol extract was proven as an antioxidant and anticancer of the uterus. The purpose of community service is to apply the potential of kenikir leaves as an anti-cancer so that it can be used by the community in RW 16 and 17 Cipageran Village, North Cimahi District. The methods used are counseling to cadres and planting kenikir plant seeds at partner locations. The results of community service obtained that the pre-test and post-test scores in RW 16 were 53 and 93, there was an increase of 76%, while the pre-test and post-test scores in RW 17 were 56 and 88, there was an increase of 57%. The conclusion of the PKM results is that there is an increase in the knowledge and understanding of the cadres regarding the use of kenikir plants in an effort to prevent cancer.